The Influence Of Price, Product Quality, And Promotion On The Decision To Purchase Jewelry At The Agung Amertha Kencana Gold Shop In Tabanan District - Pande Bgs Pradnya Widana; I Gst. A Kt. G.d. Suasana (International Journal of Economics, Business and Innovation Research, 2024)
The aim of this research is to explain the influence of price, product quality and promotion on jewelry purchasing decisions at the Agung Amertha Kencana Gold Shop, Tabanan. The population of this research is consumers who buy jewelry at the Agung Amertha Kencana Gold Shop. The technique used is purposive sampling. The number of samples determined was 130 respondents. The data collection method uses a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that the influence of price, product quality and promotion has a positive effect on jewelry purchasing decisions at the Agung Amertha Kencana Gold Shop, Tabanan. This research is expected to provide relevant and useful input for related companies in efforts to improve company performance through the prices offered, product quality and promotions. In order to increase company profitability by developing innovative programs.